Структурний аналіз системи забезпечення екологічної та природно-техногенної безпеки України - Kachinskiy, A. B.; Agarkova, N. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
The application of the binary relations (Q-analysis) theory for the investigation of the system of environmental and natural-technogenic safety maintenance is considered. From the point of view of the system analysis the connections between elements of such system are the means of influence of its elements at each other and their interaction among themselves which causes system functioning in space and time. The basic principles of creating the model of structural coherence of the system of ecological safety maintenance are presented on the example of two sets: sets of threats of emergency situations occurrence and sets of mechanisms of their prevention and elimination. Interaction between sets of system is considered on the basis of a complex as a whole, considering the existing connections between elements of system of ecological safety. Elements connectivity of system of ecological and natural and technogenic safety maintenance is investigated, numerical values eccentricity, p-holes are calculated and measures of complexity of an ecosystem elements complex are analyzed.